Analysis for corruption and decentralization (Case study: earlier decentralization era in Indonesia) - Joko Tri Haryanto; Esther Sri Astuti S.A. (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
In many countries, relationship between decentralization of government activities and the extent of rent extraction by private parties is an important element in the recent debate on institutional design. The topic of corruption was actively, openly and debated in Indonesia by government, its development partners, and a broadly based group of political and civil society leaders are engaged in meetings and exchange on a daily basis. In the ongoing debate on corruption a lot of attention is paid to the role of public sector salaries, particularly in the decentralization era. Based on this phenomenon, the authors want to analyze the relationship between corruption and decentralization. Using OSL model, we can find a very strong and consistent positive association between the two variables across a sample of region, thereby providing some support for theories of decentralization that emphasize its benefits. This association is robust to controlling for a wide range of potential sources of omitted variable bias as well as endogeneity bias. Keywords: Corruption, Decentralization, OSL Model Abstrak.Di banyak negara, hubungan antara desentralisasi pemerintah dan tingkat ekstraksi sewa oleh pihak swasta merupakan elemen penting dalam perdebatan baru pada desain institusional. Topik korupsi secara aktif, terbuka dan diperdebatkan di Indonesia oleh Pemerintah, mitra pembangunan, dan kelompok berbasis luas dari para pemimpin politik dan masyarakat sipil yang terlibat dalam pertemuan dan pertukaran setiap hari. Dalam perdebatan tentang korupsi banyak perhatian diarahkan untuk peran gaji sektor publik, terutama di era desentralisasi. Berdasarkan fenomena ini, penulis ingin menganalisis hubungan antara korupsi dan desentralisasi. Menggunakan OSL model, kita dapat menemukan hubungan positif yang sangat kuat dan konsisten antara dua variabel di seluruh sampel dari daerah, sehingga memberikan beberapa dukungan untuk teori desentralisasi yang menekankan manfaat. Asosiasi ini adalah kuat untuk mengendalikan berbagai kemungkinan potensial dari upaya menghilangkan sebagian variabel serta bias endogenitas. Kata Kunci: Korupsi, Desentralisasi, OSL Model REFERENCES,Ades, Alberto and Di Tella, Rafael, 1994, “Competition and corruption” Institute of Economics and Statistics Discussion Papers 169. University of Oxford.____, 1995, “National champions and corruption: some unpleasant competitiveness arithmetic”.University of Oxford. Photocopy.Barro, Robert, 1992, “Human capital and economic growth”. in policies for long run economic growth. Federal Reserve bank of Kansas City: 199-216.____, 1990, “Government spending in a simple model of endogenous growth.” Journal of Economy, 98, no.5, part 2, S103-S125.Bhagwati, Jagdish, 1982, “Directly unproductive, profit-seeking (dup) activities.” Journal of Political Economy, 90, no.5.Clemets, Benedict, Rejane Hugounenq, and Gerd Schwartz, 1995, “Government subsidies: concept, international trends and reform options”, IMF Working Papers 95/91. Washington, DC: International Monetary Fund.Easterly, William, 1990, “Endogenous growth in developing countries with government induced distortions.” In Vittorio Corbo, Stanley Fischer and Steve Webb, Policies to Restore Growth. Washington DC: The World Bank.Fisman, Raymond, and Roberta Gatti, 2002, “Decentralization and corruption: evidence across countries”, Journal of Public Economics 83: 325-345.Hague, Nadeem Ui, and Ratna Sahay, 1996, “Do government wage cuts close budget deficits? IMF Working Papers 96/19. Washington, DC: International Monetary Fund.Hines, James, 1995, “Forbidden payment: foreign bribery and american business.” NBER Working Papers 5266. Cambridge, MA: National Bureau of Economic Research.Keefer, Philip, and Stephen Knack, 1995, “Institutions and economic performance: cross-country tests using alternative institutional measures.” Economics and Politics.Kraay, Aart, and Van Rijckeghem, Caroline, 1995, “Employment and wages in public sector-a cross-country study.” IMF Working Papers 95/70. Washingtin, DC: International Monetary Fund.Krueger, Anne, 1974, “The Political economy of the rent-seeking society.” American Economic Review 64, No.3 (June): 291-303.Levine, Ross and David Renelt, 1992, “A sentivity analysis of cross-country growth regressions.” American Economic Review 82, No.4 (September): 942-963.Loayza, Norman, 1996, “The economics of informal sector: a simple model and some empirical; evidence from Latin America.” The World Bank. Photocopy.Martinez. Jorge-Vazquez, F. Javier Arze, Jameson Boex, 2004, “Corruption, fiscal policy and fiscal management, USAID Report (October).Mauro, Paolo, 1995, “Corruption and growth.” Quarterly Journal of Economics CX, no.3 (August): 681-712._____, 1997, “The Effect of Corruption on growth, investment and government ex-penditure: a cross country analysis, in Corruption and the global economy, K.A. Elliot, ed., Eashington D.C., Institute for International Economics, pp.83-107._____, 1998, corruption and the composition of government expenditure, Journal of Public Economics, vol.69:263-279.Megantara, Andie and Noor Fuad, 2003, “The impact of institutional environment on public official performance: does institutional environment affect the rate of corruption?”, Jurnal Keuangan Publik vol.1, no.1 (September):1-23.Murphy, Kevin, Andrei Shleifer and Robert Vishny, 1991, “Allocation of talent: implications for growth.” Quarterly Journal of Economics, 106.Raunch, James, 1995, “Bureaucracy, infrastructure and economic growth: evidence from U.S. Cities During the Progressive Era.” American Economic Review 85, no.4 (September): 968-979.Rose-Ackerman, Susan, 1978, Corruption: a study in political economy, New York, NY: Academic Press._____, 1996, Democracy and grand corruption, International Social Science Journal, vol.48. no.3._____, 1997, Corruption and development, Paper presented at the annual Bank Conference on Development Economics, Washington D.C._____, 1999, Corruption and government: causes, consequences and reform, Cambridge University Press.Sachs, Jeffrey, and Warner, Andrew, 1995, “Natural resource abundance and economic growth.” NBER Working Papers 5398. Cambrdge, MA: National Bureau of Economic Research.Shleifer, Andrei, and Robert W. Vishny, 1993., Corruption, the quarterly journal of economics, 108 (August): 599-617.Tanzi, Vito, 1994, “Corruption, governmental activities and markets.” IMF Working Papers 94/99. Washington, DC: International Monetary Fund.Taylor, Charles L. and Michael C Hudson, 1972, World handbook of political and social indicators. Ann Arbor, MI: ICPSR.Treisman, Daniel, 2000, “The causes of corruption: a cross-national study”, Journal of Public Economics 76: 399-457.Tullock, Gordon, 1967, “The welfare costs of tarriffs, monopolies and theft.” Western Economic Journal5.Vernon, Henderson, and Ari Kuncoro, 2006, “Sick of local government corruption” Vote Islamic”, NBER Working Paper 12110 (March): 1-41.